Coherent vibrational modes promote the ultrafast internal conversion and intersystem crossing in thiobases. Issue 36 (12th September 2022) - Teles-Ferreira, Danielle Cristina; van Stokkum, Ivo HM; Conti, Irene; Ganzer, Lucia; Manzoni, Cristian; Garavelli, Marco; Cerullo, Giulio; Nenov, Artur; Borrego-Varillas, Rocío; de Paula, Ana Maria
Abstract : The relaxation to the triplet state in thiobases is mediated by conical intersections promoted by vibrational coherences through the population of an intermediate singlet state. Abstract : Thionated nucleobases are obtained by replacing oxygen with sulphur atoms in the canonical nucleobases. They absorb light efficiently in the near-ultraviolet, populating singlet states which undergo intersystem crossing to the triplet manifold on an ultrashort time scale with a high quantum yield. Nonetheless there are still important open questions about the primary mechanisms responsible for this ultrafast transition. Here we track both the electronic and the vibrational ultrafast excited-state dynamics towards the triplet state for solvated 4-thiothymidine (4TT) and 4-thiouracil (4TU) with sub-30 fs broadband transient absorption spectroscopy in the ultraviolet. A global and target analysis allows us to simultaneously resolve the contributions of the different electronically and vibrationally excited states to the whole data set. Our experimental results, combined with state-of-the-art quantum mechanics/molecular mechanics simulations and Damped Oscillation Associated Spectra (DOAS) and target analysis, support that the relaxation to the triplet state is mediated by conical intersections promoted by vibrational coherences through the population of an intermediate singlet state. In addition, the analysis of the coherent vibrational dynamics reveals that, despite sharing the same relaxation mechanism and similar chemical structures, 4TT and 4TU exhibit rather different geometrical deformations, characterized by the conservation of planarity in 4TU and its partial rupture in 4TT.